A comparative analysis of two methods of wax treatment for a waxy oil in Southwest Trinidad. (16th February 2019) - Persad, Niran; Hosein, Raffie; Jupiter, Andrew
Abstract: When oil flows into the wellbore, pressure, and temperature decreases. This causes paraffin (wax) to precipitate into the oil and to deposit in production tubings, which negatively affect oil production. Wax deposition can be mitigated by the application of passive energy waves or chemical solvents. In this study, both methods of wax treatment were tested on a waxy oil well in Trinidad. Production outputs and economics showed that chemical solvent injection was the more feasible method. However, passive energy wave application enhanced oil properties, oil-water separation and showed notable success in preventing wax deposition.